2022
DOI: 10.3390/environments9100127
|View full text |Cite
|
Sign up to set email alerts
|

Role of Altitude in Formation of Diatom Diversity of High Mountain Protected Glacier Lakes in the Kaçkar Mountains National Park, Rize, Turkey

Abstract: The benthic diatom assemblages of the glacier Avusor Great Lake and Koçdüzü Great Lake were investigated in August 2019. A total of 71 diatom species belonging to 34 genera were determined in the samples, 49 species from Avusor Great Lake and 37 from Koçdüzü Great Lake. Only 15 diatom species were common to both lakes. Total floristic similarity between the neighbouring lakes was only 21.12%. Genera with the highest number of species were Eunotia (8), Gomphonema (6), Pinnularia (6), Navicula (5) and Aulacoseir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
(69 reference statements)
2
11
0
Order By: Relevance
“…Moreover, species belonging to genera Gomphonema, Navicula , and Encyonema constituted the majority of high ALT optima species in HEF. This result was similar to the study of Şahin and Barinova (2022), which reported a high occurrence of Gomphonema and Navicula species in other high mountain lakes in Türkiye.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, species belonging to genera Gomphonema, Navicula , and Encyonema constituted the majority of high ALT optima species in HEF. This result was similar to the study of Şahin and Barinova (2022), which reported a high occurrence of Gomphonema and Navicula species in other high mountain lakes in Türkiye.…”
Section: Discussionsupporting
confidence: 92%
“…high ALT optima species in HEF. This result was similar to the study of Şahin and Barinova (2022), which reported a high occurrence of…”
Section: Diatom Indicessupporting
confidence: 92%
See 3 more Smart Citations